Pelatihan Peningkatan Kapasitas Stakeholder dalam Menyusun Strategi City Branding - Mulyasari Agustini, Prima; Widiastuti, Tuti (Indonesian Journal for Social Responsibility, 2020)
Brand is an important concept in the marketing of products, booth goods and services. Giving a city a brand is needed to provide an identity for the city. With a strong brand, a city can "sell itself" and open up more extensive employment opportunities, both through tourism excellence (culinary, tourism, handicraft, arts, and culture), as an education center, as well as industry excellence that has the potential to attract investors inside and outside country. Banda Aceh, which is reported strictly with Islamic values, often makes this city unworthy of being a tourist destination. By promoting Islamic tourism, Banda Aceh still lacks in tourist arrivals, though many of Banda Aceh's culture and tourist destinations are fascinating to visit. Given the importance of communicating the superiority of destination related to Banda Aceh, stakeholder training needs to be developed in developing a city branding strategy. Stakeholders have an essential role in promoting the image of the city, primarily through various media. This training focuses on providing insights and knowledge, as well as skills in developing attractive and effective city branding strategies through multiple media to communicate the image of Banda Aceh.